2017
DOI: 10.19182/bft2016.328.a31302
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Plus Trees for Genetically Improved Teak Varieties Produced in Benin and Togo

Abstract: RÉSUMÉ SÉLECTION D'ARBRES « PLUS » POUR LA PRODUCTION DE VARIÉTÉS DE TECK GÉNÉTIQUEMENT AMÉLIORÉES AU BÉNIN ET AU TOGOCette étude vise la sélection d'arbres « plus » sur la base des caractères dendrométriques et des propriétés du bois dans des plantations de teck au Bénin et au Togo. La croissance de 569 arbres dans 5 forêts au Togo et 90 arbres dans 3 forêts au Bénin a été évaluée en mesurant le diamètre à hauteur de poitrine, la hauteur totale et la hauteur du fût. Les propriétés suivantes du bois ont été év… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It indicated that the spacing was an important aspect of increasing forest yield both forest productivity and forest economic value (Budiadi et al 2017;Seta et al 2021). It can also interact with clones to provide various wood properties (Kokutse et al 2016) by affecting the quality (Tun et al 2018). Current research on the impact of spacing on the growth, carbon sequestration, and wood quality of teak was carried out separately.…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that the spacing was an important aspect of increasing forest yield both forest productivity and forest economic value (Budiadi et al 2017;Seta et al 2021). It can also interact with clones to provide various wood properties (Kokutse et al 2016) by affecting the quality (Tun et al 2018). Current research on the impact of spacing on the growth, carbon sequestration, and wood quality of teak was carried out separately.…”
Section: Introductionmentioning
confidence: 99%
“…In each site, trees were selected on the basis of criteria defined by Kokutse et al [17]. It is about: (i) merchantable height up of a minimum 3 meters, without apparent defects (pitchfork, fluting, bump, parasite attack, etc.…”
Section: Data Collectionmentioning
confidence: 99%
“…For the best result of selecting plus trees, concerned populations must be mature as stability in flowering in the present study site and grown in homogenous conditions [17][18][19]. When a tree is mature, their growths on stem diameter, stem height, and crown diameter are negligible.…”
Section: Fig 3 a Number Of Trees In Different Categories Of Productmentioning
confidence: 99%